2004
DOI: 10.1096/fj.03-0869fje
|View full text |Cite
|
Sign up to set email alerts
|

Alpha syntrophin deletion removes the perivascular but not the endothelial pool of aquaporin‐4 at the blood‐brain barrier and delays the development of brain edema in an experimental model of acute hyponatremia

Abstract: The formation of brain edema, commonly occurring as a potentially lethal complication of acute hyponatremia, is delayed following knockout of the water channel aquaporin-4 (AQP4). Here we show by high-resolution immunogold analysis of the blood-brain-barrier that AQP4 is expressed in brain endothelial cells as well as in the perivascular membranes of astrocyte endfeet. A selective removal of perivascular AQP4 by alpha-syntrophin deletion delays the buildup of brain edema (assessed by Diffusion-weighted MRI) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
194
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(206 citation statements)
references
References 29 publications
10
194
1
Order By: Relevance
“…We interpret this finding to suggest that the immunogold signal over endothelium [as recorded in the present study and in that of AmiryMoghaddam et al (8)] represents antibody binding to AQP4 molecules embedded in the endfoot membrane. The endfoot membrane and abluminal endothelial cell membrane are separated by a basal lamina whose width is comparable to the length of the antibody bridge between epitope and gold particle (13).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We interpret this finding to suggest that the immunogold signal over endothelium [as recorded in the present study and in that of AmiryMoghaddam et al (8)] represents antibody binding to AQP4 molecules embedded in the endfoot membrane. The endfoot membrane and abluminal endothelial cell membrane are separated by a basal lamina whose width is comparable to the length of the antibody bridge between epitope and gold particle (13).…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, some studies have pointed to the possible presence of an endothelial pool of AQP4 in brain (8)(9)(10). This would be missing in constitutive knockout animals along with the endfoot pool, complicating the analysis of water transport at the blood-brain interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the data suggest that AQP4 not only mediates water influx but also is essential for initiating signaling events associated with edema formation. This may explain the rather pronounced protective effect of Aqp4 KO or AQP4 mislocalization in stroke models (8,20). It is well-known that water passes through the lipid bilayer of the plasma membrane (although to a limited extent compared with the water flux through aquaporin channels) and that diffusion also occurs through the thin slits that separate the astrocyte endfeet.…”
Section: Discussionmentioning
confidence: 99%
“…99 A recent report suggests that endothelial AQP4 can be seen in ␣-syntrophin knockout mice, and that endothelial expression may be seen in these mice when the water channel protein is lost from the adjacent membrane of the glial foot process. 98 These authors further indicated that endothelial AQP4 expression was quite low and FIG. 13.…”
Section: Fig 12mentioning
confidence: 97%